Medium-Sized cities and urban environmental inequalities. Case studies from South America - Brites, Walter F. (2025)
Introduction: The article discusses a dimension that has been little problematised in the study of cities: urban environmental inequalities. To this end, a theoretical discussion is presented that places urban policy at the epicentre of the problem. On the one hand, it is argued that the benefits associated with high environmental quality environments and the disadvantages of polluted environments are not randomly distributed, but are due to socio-economic and spatial processes. Objective: To understand and describe urban environmental inequalities with a focus on the implementation of policies, programmes or projects in the urban space. Methodology: Based on a case study of four cities (Cochabamba, Ciudad del Este, Valparaíso and Viña del Mar), using documentary exploratory research and consultations with technicians and specialists, including a review of environmental policies. Conclusions: The reflection highlights the inequalities generated by urban policies that unbalance the quality of life and the habitat of the popular sectors, where the costs of pollution are not addressed to the poorest populations, highlighting how the adversities of the polluted environment, exposure to risks and vulnerability of the environment create new inequalities that deepen the disadvantages.